4
$\begingroup$

How to prove that

$$\sum_{n=1}^\infty\frac{H_n^4}{n^2}=\frac{979}{24}\zeta(6)+3\zeta^2(3)\ ?$$ $$\sum_{n=1}^\infty\frac{H_n^2H_n^{(2)}}{n^2}=\frac{41}{12}\zeta(6)+2\zeta^2(3)\ ?$$ where $H_n^{(p)}=1+\frac1{2^p}+\cdots+\frac1{n^p}$ is the $n$th generalized harmonic number of order $p$.

We can find these two sums nicely evaluated in the book Almost Impossible Integrals, Sums and series page 429 using pure series manipulations and I managed to find their closed forms using integration and some harmonic-number identities ( Solution will be posted in the answer section ), but can we tackle them by other means like contour integration or the $\arcsin^4x$ identity just like what @nospoon did in his solution here, where he mentioned the result of the second sum in $(4)$ but not the first one, or by any other way?

Thanks .

$\endgroup$
  • 2
    $\begingroup$ Are you going to post every single problem of the whole book here, if we let you? :P However, it is interesting anyway to see different approaches (+1) By the way, I finally got my very own version of Valean's (Almost) Impossible Integrals, Sums and Series :) $\endgroup$ – mrtaurho Aug 1 at 20:23
  • $\begingroup$ @mrtaurho all these results I posted are known in the literature and I use the book just as a reference and I learn a lot from it. Plus I post just the advanced problems. Congrats on getting the book have fun with it. $\endgroup$ – Ali Shather Aug 1 at 21:01
2
$\begingroup$

To compute these two sums, we are going to establish two relations and solve them by elimination.

First Relation:

From here we have $$-\int_0^1x^{n-1}\ln^3(1-x)\ dx=\frac{H_n^3+3H_nH_n^{(2)}+2H_n^{(3)}}{n}$$

Multiply both sides by $\frac{H_n}{n}$ then sum both sides from $n=1$ to $\infty$ to get

\begin{align} R_1&=\sum_{n=1}^\infty\frac{H_n^4}{n^2}+3\sum_{n=1}^\infty\frac{H_n^2 H_n^{(2)}}{n^2}+2\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}=-\int_0^1\frac{\ln^3(1-x)}{x}\sum_{n=1}^\infty\frac{H_n}{n}x^n\ dx\\ &=-\int_0^1\frac{\ln^3(1-x)}{x}\left(\frac12\ln^2(1-x)+\operatorname{Li}_2(x)\right)\ dx\\ &=-\frac12\int_0^1\frac{\ln^5(1-x)}{x}\ dx-\int_0^1\frac{\ln^3(1-x)\operatorname{Li}_2(x)}{x}\ dx\\ &=60\zeta(6)-I \end{align}

Then $$\boxed{R_1=\sum_{n=1}^\infty\frac{H_n^4}{n^2}+3\sum_{n=1}^\infty\frac{H_n^2 H_n^{(2)}}{n^2}+2\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}=60\zeta(6)-I}$$.


Second Relation:

From here, we have

$$-\frac{\ln^3(1-x)}{1-x}=\sum_{n=1}^\infty x^n\left(H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}\right)$$

Divide both sides by $x$ then integrate from $x=0$ to $x=y$, we get

$$-\int_0^y\frac{\ln^3(1-x)}{x(1-x)}\ dx=\sum_{n=1}^\infty \frac{y^n}{n}\left(H_n^3-3H_nH_n^{(2)}+2H_n^{(3)}\right)$$

Now multiply both sides by $-\frac{\ln(1-y)}{y}$ then integrate from $y=0$ to $y=1$ and use the fact that $-\int_0^1 y^{n-1}\ln(1-y)\ dy=\frac{H_n}{n}$, we get

\begin{align} R_2&=\sum_{n=1}^\infty\frac{H_n^4}{n^2}-3\sum_{n=1}^\infty\frac{H_n^2 H_n^{(2)}}{n^2}+2\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}=\int_0^1\int_0^y\frac{\ln^3(1-x)\ln(1-y)}{xy(1-x)}\ dx\ dy\\ &=\int_0^1\frac{\ln^3(1-x)}{x(1-x)}\left(\int_x^1\frac{\ln(1-y)}{y}\ dy\right)\ dx\\ &=\int_0^1\frac{\ln^3(1-x)}{x(1-x)}\left(\operatorname{Li}_2(x)-\zeta(2)\right) dx\\ &=\int_0^1\frac{\ln^3(1-x)}{x}\left(\operatorname{Li}_2(x)-\zeta(2)\right) dx+\underbrace{\int_0^1\frac{\ln^3(1-x)}{1-x}\left(\operatorname{Li}_2(x)-\zeta(2)\right) dx}_{IBP}\\ &=I-\zeta(2)\int_0^1\frac{\ln^3(1-x)}{x}\ dx-\frac14\int_0^1\frac{\ln^5(1-x)}{x}\ dx\\ &=I+6\zeta(2)\zeta(4)+30\zeta(6)\\ &=I+\frac{81}{2}\zeta(6) \end{align}

Then $$\boxed{R_2=\sum_{n=1}^\infty\frac{H_n^4}{n^2}-3\sum_{n=1}^\infty\frac{H_n^2 H_n^{(2)}}{n^2}+2\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}=I+\frac{81}{2}\zeta(6)}$$.


Therefore

\begin{align} \sum_{n=1}^\infty\frac{H_n^4}{n^2}&=\frac{R_1+R_2}{2}=\frac{201}{4}\zeta(6)-2\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}\\ &=\frac{201}{4}\zeta(6)-2\left(\frac{227}{48}\zeta(6)-\frac32\zeta^2(3)\right)\\ &=\frac{797}{24}\zeta(3)+3\zeta^2(3) \end{align}

where the value of $\sum_{n=1}^\infty\frac{H_nH_n^{(3)}}{n^2}$ is calculated here.


and

\begin{align} \sum_{n=1}^\infty\frac{H_n^2H_n^{(2)}}{n^2}&=\frac{R_1-R_2}{6}=\frac{13}{4}\zeta(6)-\frac13I \end{align}

and the remaining integral can be approached as follows:

\begin{align} I&=\int_0^1\frac{\ln^3(1-x)\operatorname{Li}_2(x)}{x}\ dx\overset{1-x\ \mapsto\ x}{=}\int_0^1\frac{\ln^3x\operatorname{Li}_2(1-x)}{1-x}\ dx\\ &=\int_0^1\frac{\ln^3x}{1-x}(\zeta(2)-\ln x\ln(1-x)-\operatorname{Li}_2(x))\ dx\\ &=\zeta(2)\int_0^1\frac{\ln^3x}{1-x}\ dx-\int_0^1\frac{\ln^4x\ln(1-x)}{1-x}\ dx-\int_0^1\frac{\ln^3x\operatorname{Li}_2(x)}{1-x}\ dx\\ &=-6\zeta(2)\zeta(4)+\sum_{n=1}^\infty H_n\int_0^1x^n\ln^4x\ dx-\sum_{n=1}^\infty H_n^{(2)}\int_0^1 x^n \ln^3x \ dx\\ &=-\frac{21}2\zeta(6)+24\sum_{n=1}^\infty\frac{H_n}{(n+1)^5}+6\sum_{n=1}^\infty\frac{H_n^{(2)}}{(n+1)^4}\\ &=-\frac{21}2\zeta(6)+24\sum_{n=1}^\infty\frac{H_n}{n^5}-24\zeta(6)+6\sum_{n=1}^\infty\frac{H_n^{(2)}}{n^4}-6\zeta(6)\\ \end{align}

Substituting $\sum_{n=1}^\infty\frac{H_n}{n^5}=\frac74\zeta(6)-\frac12\zeta^2(3)$ and $\sum_{n=1}^\infty\frac{H_n^{(2)}}{n^4}=\zeta^2(3)-\frac13\zeta(6)$ ( proved here), we get

$$I=-\frac12\zeta(6)-6\zeta^2(3)$$

Consequently $$\sum_{n=1}^\infty\frac{H_n^2H_n^{(2)}}{n^2}=\frac{41}{12}\zeta(6)+2\zeta^2(3)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.